PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP MINAT BELAJAR PESERTA DIDIK - Husheini Fadhil; Firdaus Suhaemi; Ibrahim; Maria Ulfah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of digital technology has made social media an integral part of students' daily lives. Social media offers opportunities to access information and educational resources, but uncontrolled use may also affect students' concentration, discipline, and interest in learning. This study aimed to determine the effect of social media use on students' learning interest, measure the magnitude of its contribution, and identify strategies for improving learning interest through the educational use of social media. This study employed a quantitative approach with a survey method. The population consisted of 156 students at SMK Pariwisata Cipta Karya, from which 61 respondents were selected as the research sample. Data were collected through observation, questionnaires, interviews, and documentation and analyzed using Pearson Product Moment correlation and regression analysis. The results showed a positive and significant relationship between social media use and students' learning interest, with a correlation coefficient of 0.615 and a significance value of 0.000 < 0.05. The coefficient of determination (R Square) was 0.378, indicating that social media use contributed 37.8% to variations in students' learning interest, while the remaining 62.2% was influenced by other factors outside this study. The t-test obtained a value of 5.989, while the F-test obtained a value of 35.874, both with a significance value of 0.000 < 0.05. Therefore, educational, purposeful, and controlled use of social media can support students' learning interest.